Sponsor ownership and IPO initial return: evidence from Pakistan stock exchange. Issue 1 (26th August 2021) - Mehmood, Waqas; Mohd-Rashid, Rasidah; Ahmad, Abd Halim; Amin, Saqib
Abstract : Purpose: The purpose of this paper was to examine whether or not the sponsor lock-up ratio, lock-up period, regulation changes and interaction variable (oversubscription [OSR]) affected initial public offering (IPO) initial return. Design/methodology/approach: A complete sample of 111 listed IPOs in Pakistan stock exchange from 1996 to 2018 was incorporated. Based on the cross-section data, this paper estimated using ordinary least square and quantile least square for robustness. In addition to that, this paper estimated the data using stepwise least square to inspect the signalling aspect of the lock-up ratio, lock-up period and regulation changes on IPO initial return. Findings: This study showed that the lock-up ratio, lock-up period and regulatory changes had a positive impact on the IPO's initial return. Furthermore, the assertion of interaction variable (regulation changes × OSR) and (lock-up period × OSR) was a negatively significant factor in influencing the IPO's initial return. The results of this paper were robust to endogeneity bias. Practical implications: The finding of this study proposed that sponsors of IPOs can be a strong signal of risk or quality, which was consistent with the signalling theory prediction. Concurrently, investors must be aware of the total proportions of lock-up ratio so that they can estimate the chances of getting the highest initial return on IPOs. From the regulators' point of view, it is suggested that the lock-up ratio and the lock-up period should be determined with a deeper understanding and incorporated into the equity guidelines as it is evident that these factors are priced by the market. Originality/value: Studies on the effect of sponsors have always been centred on well-recognized firms. Therefore, using the IPO samples listed in Pakistan, this paper contributes to the IPO literature by investigating the lock-up ratio of the sponsor, the lock-up period and the regulatory changes to the initial IPO return. Additionally, OSR has been introduced as an interaction variable among the sponsors' lock-up period and regulations changes to explain the ongoing IPO initial return phenomenon.